Synthesis, characterization, and electrochemical, spectroelectrochemical and electrical measurements of novel ball-type four 1,1 '-methylenedinaphthalen-2-ol bridged metal-free, zinc(II) and cobalt(II), and metal-free clamshell phthalocyanines - ÖZKAYA, ALİ RIZA; ODABAŞ, ZAFER (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The new ball-type bisplithalocyanines [metal-free 6, Zn(II) 7 and Co(II) 8] were synthesized from the corresponding 4,4'-[1,1'-methyl-enebis(naphthalene-2,1-diyl)]bis(oxy)di-phthalonitrile 4, which can be obtained from the reaction of 4-nitrophthalonitrile (2) with 1,1'-methylenedinaphthalen-2-ol 3. A novel clamshell type bisphthalocyanine 5 was synthesized from compound 4 and 4,5-bis(hexylthio)phthalonitrile 1. The novel compounds have been characterized by elemental analysis, UV/Vis, IR, H-1 NMR and MALDI-TOF Mass spectroscopies. The electrochemical and spectroclectrochernical measurements showed the formation of various mixed-valence oxidation and reduction species, due to the strong intramolecular interactions between the two phthalocyanine rings, especially in the ball-type phthalocyanines. The conduction properties of the compounds have been examined by d.c. and impedance spectroscopy measurements as function of temperature and frequency. D.c. conductivity, measured between 290 and 480 K, is thermally activated with the activation energy ranging between 0.62 and 0.84 eV. The a.c. results gave a power law behaviour, sigma(a.c.) = A(T)w(s), in which the frequency exponent s decreases with temperature for 6, 7 and 8. The bulk resistance of the samples was derived from complex impedance spectra. It was found that the bulk resistance shows a typical negative temperature coefficient of resistance, decreasing with a rise in temperature, like that of a semiconductor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ball type; clamshell; bisphthalocyanine; synthesis; spectroelectrochemistry; impedance spectroscopy; GAS-SENSING PROPERTIES; DECKER LUTETIUM(III) PHTHALOCYANINE; BINUCLEAR PHTHALOCYANINES; BISPHTHALOCYANINATO COMPLEXES; SEMICONDUCTORS; SUBSTITUENTS; CONDUCTION; SPECTRA; FILM